To evaluate the prevalence of edentulousness, the present prosthetic status, and the need for prosthetic treatment in the population of Garhwa, Jharkhand - Amit Kumar Mishra (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aimed to evaluate the prevalence of edentulousness, the present prosthetic status, and the need for prosthetic treatment in the population of Garhwa, Jharkhand. Materials and Methods: A descriptive cross-sectional study was conducted among the population of Garhwa, Jharkhand. The sample size included 460 subjects belonging to an age group of 25 years and above. Detailed case history and thorough dental examination was done and all the findings were recorded and compiled. Each subject was interrogated with the help of a predesigned closed ended questionnaire. Results: A total of six patients were completely edentulous, while 55.04% of males and 42.80% of females were partially edentulous. All patients who were completely edentulous were denture wearer, while among partially edentulous patients, 6.31% of males and 3.15% of females had RPD and 13.68% and 6.31% of males and females, respectively, had FPD as prosthesis. Prosthetic status of females was better than males In a comparison of prosthetic status between male and female, out of 460 subjects, 195 subjects opted for prosthesis, in which 117 were male and 78 were female. Conclusion: Community-based oral health education programs should be conducted to improve patients' oral health knowledge. Educating patients regarding the limitations of prosthesis as mechanical substitutes for natural teeth must be a continuing process from the initial patient contact until adjustments are completed.